Penerapan Kode Etik Pustakawan di Perpustakaan Universitas Negeri Padang - Agniken, Sinda; Nelisa, Malta (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2015)
Writing this article aims to describe (1) the implementation of the code of ethica librarian at the Librarian of the University of Padang; (2) the obstacles ancounteredin the implementation of the code of ethics oflibrarians and describe the efforts made to overcome the obstacles in the implementation of the code of ethics of librarians. Data collected by observation and interview with the librarian at the Library of the State University of Padang. Data analisis was done descriptively, it can be concluded that (1) Librarian Padang State University has been applying the basic attitude of librarians with the users, the relationship between librarians, community relations. But not all librarians are able to apply the code of conduct in the workplace, there are still many librarians who only know the code of ethics of librarians without applying the code of ethics of librarians; (2) in moking application of the Code Librarian at the Library of the University of Padang still has many obstacles, obstacles encounteredis the lack of know ledge of librarians about the basic attitude of librarians and do not know the code of ethics as a librarian professionals, lack of talent librarians to communicate and get along, so librarian hostility in serving meanwhile, efforts to be made by librarians terkain this obstacle is not maximized.Â Keywords: Implementation, code ethics